Synthesis and properties of branched polyethylene/high-density polyethylene blends using a homogeneous binary catalyst system composed of early and late transition metal complexes - Kunrath, Fábio A. [UNESP]; Mauler, Raquel S.; De Souza, Roberto F.; Casagrande Jr., Osvaldo L. (My University, 2002)
Branched polyethylene/high-density polyethylene blends (BPE/HDPE) with a wide range of molecular weights, melt flow indexes (MFI), and intrinsic viscosity were prepared using the homogeneous binary catalyst system composed by Ni(α-diimine)Cl2 (1) (α-diimine = 1,4-bis(2,6- diisopropylphenyl)-acenaphthenednmme) and {TpMs*}TiCl3 (2) (TpMs* = hydridobis(3-mesitylpyrazol-1-yl)(5-mesitylpyrazol-1-yl)) activated with MAO and/or TIBA in hexane at two different polymerization temperatures (30 and 55 °C) and by varying the nickel loading molar fraction (xNi). At all temperatures, a non-linear correlation between the xNi and the productivity was observed, suggesting the occurrence of a synergistic effect between the nickel and the titanium catalyst precursors, which is more pronounced at 55 °C. The molecular weight of the BPE/HDPE blends considerably decreases with increasing A1/M molar ratio. The melt flow indexes (MFI) and intrinsic viscosities (η) are strongly affected by xNi, but the melting temperatures are nearly constant. 132 ± 3 °C. Dynamic mechanical thermal analysis (DMTA) shows the formation of different polymeric materials where the stiffness varies according to the xNi and temperature used in the polymerization reaction. The surface morphology of the BPE/HDPE blends studied by scanning electron microscopy (SEM) revealed a low miscibility between the PE phases resulting in the formation of a sandwich structure after etching with o-xylene.
Keywords: BPE/HDPE blends; Ethylene polymerization; Homogeneous binary catalyst system; Synergistic effect; Ti and Ni catalysts